RELATIVITAS RAGAM ‘ĀMIYYAH DAN BAHASA DAERAH DI PONDOK MODERN - Wahyu Hanafi Putra (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
students PP. Darul Falah Sukorejo Ponorogo East Java in daily activities and institutional efforts in maintaining the local language. The method used in this research is descriptive qualitative. In sociolinguistic discourse, the birth of society diealek said influenced by several factors, including cultural, social, geographical, and religious factors. Conservative village as one of the propaganda media of Islam in the archipelago that is the character of defense will bring the role and function in preserving the local culture and promote the civilization of the nation that is supported by Islamic values. One of the conservative village combination in Ponorogo district is PP. Darul Falah Sukorejo. In its management, the students who live inconservative village are required to communicate with Arabic in various activities, thus indirectly forming the language environment. However, there is a uniqueness in the continuity of communication, namely the use of Arabic dialect 'Āmiyyah. The Āmiyyah constructions used include morphological and syntactic dimensions with a wide variety that is only understood by the students community in the conservative village. Then, in order to maintain the language of the santri area so as not to extinct, PP. Darul Falah Sukorejo provides concrete steps to ensure that local languages ​​still exist, including by establishing a language study center, regional language week, and regional cultural festivals.